Improving Students’ Ability in Writing Skill through Picture Series in SMAN 7 Kediri - Nurul Aini; Egita Ratih (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2021)
This study aims to improve the writing skills of students in class XI MIPA in 2 SMAN 7 Kediri through picture series. The objective of the study to know how picture series can improve students’ ability in writing explanation text through Picture Series. CAR is carried out through a cycle consisting of four stages, starting with planning the action, continuing with the action learning and observation activities and ends with a reflection for study and analyze data obtained through action. This research was conducted in one cycle, the criteria of success if 80% of students score above the KKM 75 and with an average score of at least 80. Data were collected from observations, tests, and documentation. The findings in this study found that the use of picture series significantly improved students' writing skills. This can be seen from the average in preliminary test score was 61.75 and the cycle test score of 80.62, increasing to 18,87 based on the criteria of success above, this research considered as successful. This research shows that therefore, using picture series can improve students' writing skills.